2022
DOI: 10.1186/s12888-022-04073-0
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatization related COVID-19 and PTSD among Chinese graduates

Abstract: Background Since COVID-19 broke out worldwide, it had caused extensive public health concerns and psychological distress, including PTSD and stigmatization towards recovered patients and people from high-risk areas. However, the association between PTSD, stigmatization and certain related factors have not been confirmed. Methods Through cluster random sampling, 946 Chinese graduates were investigated from 5 universities in Shanghai at three months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
2
0
1
Order By: Relevance
“…This result was consistent with previous studies among different populations, such as patients recovered from COVID-19 ( Mahmoudi et al., 2021 ), individuals who have experienced a mental disorder( Lewis et al., 2022 ), Ebola virus disease (EVD) survivors and healthcare workers (HCWs) ( Cénat et al., 2022 ). A study conducted in China showed a positive correlation between COVID-19 related stigma and PTSD symptoms among patients recovering from COVID-19( Gu et al., 2022 ). Stigma would lead to self-esteem and self-efficacy reduction ( Avdibegović and Hasanović, 2017 ), as well as discrimination, rejection or exclusion from the normal social environment ( Rewerska-Juśko and Rejdak, 2020 ), which finally might result in further mental health issues.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with previous studies among different populations, such as patients recovered from COVID-19 ( Mahmoudi et al., 2021 ), individuals who have experienced a mental disorder( Lewis et al., 2022 ), Ebola virus disease (EVD) survivors and healthcare workers (HCWs) ( Cénat et al., 2022 ). A study conducted in China showed a positive correlation between COVID-19 related stigma and PTSD symptoms among patients recovering from COVID-19( Gu et al., 2022 ). Stigma would lead to self-esteem and self-efficacy reduction ( Avdibegović and Hasanović, 2017 ), as well as discrimination, rejection or exclusion from the normal social environment ( Rewerska-Juśko and Rejdak, 2020 ), which finally might result in further mental health issues.…”
Section: Discussionmentioning
confidence: 99%
“…По данным Всемирной организации здравоохранения, на сегодняшний день в мире зарегистрировано более 511 млн случаев заболевания коронавирусной инфекцией, среди которых более 6,2 млн привели к летальному исходу [1]. В России число заражённых достигло 18,4 млн и продолжает расти [2].…”
Section: актуальность / Actualityunclassified
“…For instance, the South Korean government has taken a containment strategy focusing on disease prevention (14)(15)(16)(17), whereas in the U.S., a mitigation strategy was implemented at the level of government, that focused on reducing severe cases, while the stringency of the strategy differed widely depending on individual states (14,18). In addition, people of a collectivistic orientation like that of South Korea tend to show stronger risk perception and a higher sense of social responsibility toward their in-groups compared to a more individualistic culture (e.g., U.S.) (19)(20)(21), which may have impacted the psychological vulnerability during the early, adjustment stages of the pandemic. Lastly, differences in mental health care systems and accessibility to available mental healthcare in the two countries might also have contributed to different progress of anxiety/ depression during the pandemic.…”
Section: Introductionmentioning
confidence: 99%